Working for Canada : a pilgrimage in foreign affairs from the New World Order to the rise of populism - White, Geoff (Author of Working for Canada) (Beyond boundaries series, 2022)
"An officer of Global Affairs Canada from 1990-2018, Geoff White is a career expert in Canadian foreign policy. In Working for Canada he shares that expertise, illuminating the often invisible work of creating and enacting international policy from the perspective of a foreign affairs practitioner. Reflecting on the headlines, highlights, and sometimes scandals of a long and successful career, from strategic communication in the Persian Gulf War to NAFTA, Kosovo, softwood lumber, international arts promotion, Canada's relationships with South Africa and Chile, and beyond, White offers a highly readable blend of personal recollection and invaluable contextualization, situating Canada within the ever-evolving international milieu. A fascinating inside look at Canadian international affairs, Working for Canada is a memoir not to be missed."--